Developing Students' Academic Resilience to Improve Their Academic Competence in the Classroom - Saleh, Zulfa; Fitri, Susi; Marjo, Happy Karlina (Jurnal Ilmiah Global Education, 2025)
This article addresses public concerns about students' low academic competence. Academic competence encompasses the knowledge, skills, and abilities necessary for academic success. Academic resilience is a student's capacity to overcome acute or chronic difficulties in the academic environment that can be a significant obstacle to their academic success. The ability to overcome difficulties, challenges, and failures in the academic environment is hypothesized to have a significant impact on academic competence. Researchers investigated the relationship between academic resilience and academic competence in Muhammadiyah Senior High School students in East Jakarta. The number of respondents from 4 schools was 400 students. After testing for normality, homogeneity, and linearity. The results showed a positive correlation between academic resilience and students' academic competence. With a correlation coefficient of 0.480, a significance value of 0.000 (p <0.05 p <0.05 p <0.05). This indicates a fairly strong and significant positive relationship between Academic Resilience and Academic Competence. This means that the higher the Academic Resilience, the higher the Academic Competence. Academically resilient students tend to be more persistent in the face of learning obstacles, more proactive in seeking solutions, and more adaptable to changes in curriculum or learning methods. These characteristics are believed to contribute to the development of stronger academic competencies, enabling them to master subject matter, solve problems, and apply knowledge more effectively. The results of this study are expected to provide valuable insights for educational institutions in developing interventions that support increased student resilience and academic competency.